Conservative Management of Submandibular Space Infection in a 5-Year-Old Child: A Case Report - Khadka, Sanchita; Koirala, Bandana; Jaisani, Mehul Rajesh; Rai, Siddhartha (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Submandibular space infection is a potentially fatal infection that could arise as a result of odontogenic or non-odontogenic infections. The management should be prompt as the infection can spread rapidly leading to airway obstruction. A 5-year-old child reported with a complaint of swelling on the left side of the face for four days. On examination, patient had a diffuse swelling involving the left submandibular region with decreased mouth opening secondary to carious 75. The patient was administered intravenous (i.v) fluids, antibiotics and analgesics. Incision and drainage of the abscess was done extraorally under i.v sedation using midazolam with local anaesthesia followed by rubber drain placement. Patient responded to the treatment with progressive decrease in the swelling. Pulpectomy of 75 was performed followed by stainless-steel crown placement. This case highlights the importance of prompt appropriate treatment supplemented by salvage treatment to overcome the associated morbidity at this very young age.